Fertility Outcome of Surgical Recanalization of Vas Deferens in Individuals with Non Scalpel Vasectomy (NSV) - Roy, Hriday Ranjan; Islam, Nabiul; Islam, SM Saidul (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Background: Non Scalpel Vasectomy (NSV) is being widely used by Family Planning Sector of Bangladesh for male sterilization. But when young persons with NSV needs reversal of the procedure (recanalization), they become frustrated hugely affecting the family harmony. Aims and Objectives: To see the efficacy of recanalization of Vas Deferens of Non Scalpel Vasectomy (NSV) Individuals. To establish confidence on national NSV program by assuring the scope of future reversal if needed. Materials and methods: During the period of January 2017 to November 2019, we have analyzed the outcome of recanalization surgery of all cases of NSV individual which were referred to our urology team at Rangpur of Bangladesh. We excised the involved segment of Vas Deferens and stented it internally by No-1 prolene (Ethicon). Then end-to-end anastomoses were done by 7/0 vicryl (Ethicon). We collected articles from Hinari, Pubmed and Banglajol with extensive searches. We have compared our findings to the previously published articles. Result- We found 91.9% success rate in this study with positive semen production. Pregnancies were achieved in wives of 72.9% of recanalized individuals. The most common causes of unsuccessful recanalizations are more than 7 years of NSV, knot in close proximity to epididymis, two or more knots and cord like Vas Deferens. One patient had significant hematoma leading to a failed outcome, otherwise there was no mentionable complication in this series. Conclusion- Recanalization of Vas Deferens of NSV individuals can be done with high success rate and other centers of Bangladesh may take steps for further evaluation. J Bangladesh Coll Phys Surg 2021; 39(3): 167-170